2013
DOI: 10.1016/j.bjane.2013.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia for awake craniotomy: case report

Abstract: Although the maintenance of analgesia and hemodynamic stability was a challenge with the patient awake, the target-controlled infusion of propofol provided the desired level of consciousness, remifentanil titrated analgesia and sedation without drug accumulation, and the blockade with ropivacaine provided satisfactory analgesia. We conclude that the anesthetic technique was satisfactory for our patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Alternatively, Brosnan et al performed an asleep-awake-asleep craniotomy on a non-verbal patient by the use of neuronavigation and 5-aminolevulinic acid fluorescence, and postoperative examination proved an improvement in speech and cognition [ 15 ]. Bolzani et al concluded that although the maintenance of analgesia and hemodynamic stability is a challenge with an awake patient, the target-controlled infusion of anesthetic drugs can provide the needed level of consciousness, which is essential for the satisfactory outcome of the procedure [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, Brosnan et al performed an asleep-awake-asleep craniotomy on a non-verbal patient by the use of neuronavigation and 5-aminolevulinic acid fluorescence, and postoperative examination proved an improvement in speech and cognition [ 15 ]. Bolzani et al concluded that although the maintenance of analgesia and hemodynamic stability is a challenge with an awake patient, the target-controlled infusion of anesthetic drugs can provide the needed level of consciousness, which is essential for the satisfactory outcome of the procedure [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of the anaesthesiologist is to provide analgosedation and cardiorespiratory stability without interfering with electrophysiological monitoring and cognitive tests, so optimal anaesthetic management remains a challenge [6].…”
Section: Discussionmentioning
confidence: 99%
“…9,10 The use of sedation scales such as the Ramsay sedation score has helped ensure an appropriate depth of anesthesia throughout the procedure. 11,12 The disadvantages of the procedure identified are as follows: (1) possibility of a prolonged surgical procedure with awkward body positioning; (2) need for patient cooperation to evaluate language, memory, and motor skills; (3) potential for significant patient discomfort, e.g., pain, nausea and recall; and (4) potential for emergent airway management should the patient become uncooperative or when persistent seizure activity occurs. Knowledge of these consequences is the first step in addressing them during the awake phase of the procedure.…”
Section: History Of Awake Craniotomy In the Philippine General Hospitalmentioning
confidence: 99%